2016
DOI: 10.1097/jnn.0000000000000197
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Cognitive Function in Older Adults: The Mediating Effect of Depressive Symptoms

Abstract: Depressive symptoms and social networks may influence the relationship between physical activity and cognition. Using structural equation modeling, depressive symptoms and social networks were examined as mediators between physical activity and cognition in community-dwelling older adults (N = 122), with a range of cognitive abilities (e.g., normal, mild cognitive impairment). The model included age, physical activity, sedentary behavior, sleeping, social networks, depressive symptoms, and cognitive function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 57 publications
1
51
0
Order By: Relevance
“…Like vitamin D status, higher physical activity promotes cognitive functioning in older adults [ 62 ]. A very recent study by Lee et al [ 63 ] has revealed that impaired TUG performance was associated with increased risk of all causes of dementia, which remains in line with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Like vitamin D status, higher physical activity promotes cognitive functioning in older adults [ 62 ]. A very recent study by Lee et al [ 63 ] has revealed that impaired TUG performance was associated with increased risk of all causes of dementia, which remains in line with our results.…”
Section: Discussionmentioning
confidence: 99%
“…However, PA and exercise have been found to reduce symptoms of depression and anxiety in both clinical [15,16] and non-clinical populations [17]. Studies suggest a link between PA, cognitive function, and depressive symptoms [18,19], indicating that PA may improve cognitive function among individuals suffering from depression [18] or with high levels of depressive symptoms [19]. A large prospective study found that both low and high intensity leisure-time PA reduces the risk of dementia-related mortality among individuals with and without distress [20].…”
Section: Introductionmentioning
confidence: 99%
“…important to increase physical activity in people from LMICs Cognitive impairment also appears to influence physical activity participation among people with depression(53), and increasing physical activity might help improve both of these conditions(54,55). Since cognitive impairment and depression often coexist(56), additional support may be required to encourage people with coexisting depression and cognitive impairment to become more active.Overcoming all of these potential barriers may be important for increasing physical activity in LMICs among people with depression.…”
mentioning
confidence: 99%